INDONESIAN TRANSNATIONAL DOMESTIC WORKERS: LIFE EXPERIENCES AND STRATEGIES FOR OVERCOMING POST-CRISIS CHALLENGES - Tandos, Rosita; El-Zieny, Asma (JURNAL AL-IJTIMAIYYAH, 2025)
This study explores the life experiences of returned Indonesian female migrant domestic workers (FMDWs) residing in coastal areas, with a particular focus on the challenges they face upon reintegration and their strategies for overcoming post-crisis adversities. Conducted in Indramayu District, West Java, the research adopts a qualitative approach involving demographic surveys of 105 participants and in-depth interviews with 20 selected respondents. The findings reveal that returned FMDWs experience significant economic hardship, health vulnerabilities, and social insecurity, often exacerbated by gender-based roles and limited institutional support. Despite these constraints, many women demonstrate resilience and agency in rebuilding their lives. The study, framed through a gender-sensitive social work perspective, emphasizes the need for multi-level interventions including legal reform, family and community engagement, and stronger collaboration between sending and receiving countries. The article concludes by proposing sustainable reintegration and empowerment strategies to enhance the well-being of FMDWs and strengthen the resilience of their communities.